Modelagem da erosão hídrica pelo método de erosão potencial em uma sub-bacia hidrográfica de referência no Sul de Minas Gerais - Tavares, André Silva (2017)
The ability of the soil to promote socioeconomic and environmental sustainability is linked to its ability to provide nutrients and support for the biosphere and terrestrial ecosystems. This ability depends on the balance between the physical, chemical and biological conditioning of the soil under the influence of climatic, geomorphological, anthropic and chronological factors. Therefore, soil deterioration processes can be evaluated based on the aid of environmental indicators. Soil loss is an effective indicator for assessing the health and functioning of the terrestrial ecosystem, since erosion is one of the major factors causing soil degradation in the world and is a social, economic and environmental challenge to be overcome. Therefore, estimating the potential for soil losses and sediment production in the different operations of the Laje Stream Hydrographic Sub-basin, which flows into the Furnas Hydroelectric Power Plant reservoir, south of Minas Gerais, is an essential task for the planning, Management and protection of soil and water resources, as well as predicting whether natural resources are being used above the carrying capacity. To estimate the potential erosion, the Potential Erosion Method was used, incorporating its algorithms in the Erosion and Flow Intensity software, which provided greater agility and reliability in the measurement of results. The model was applied in Geographic Information System with the aid of geoprocessing, and the main factors described in the form of digital maps and information plans. The digital maps were derived from the Digital Elevation Model, from chemical and physical soil analysis, field data and information obtained from the specialized literature. The coefficient suggesting the mean erosion potential was calculated as 0.37, or deterioration category IV, indicating weak degree of erosion. Potential mean soil losses were equivalent to those obtained by the Revised Universal Soil Loss Equation in the same subbasin, with a mean of 1.52 Mg ha-¹ year-¹ and a total potential loss of soil of 668.26 Mg ha-¹ year-¹. The total potential loss in this research was 649.31 Mg year-¹ for a 100 year return period. The discharge of sediment that reached the defluvium was 60 Mg year-¹, that is, 9.3% of the total potential losses reached the depositional areas or watercourses. The mean of potential soil losses in this model was 1.46 Mg ha-¹ year-¹. The results are considered satisfactory and support new studies with the application of the Potential Erosion Method in Brazil.